Altigena malihkaia, a new species of Labeonini (Teleostei: Cyprinidae) from the Irrawaddy River basin in Myanmar - Zheng, Lan-Ping; Qin, Tao; Chen, Xiao-Yong (Zootaxa, 2018)
Altigena malihkaia, new species, is described from the Mali Hka River, a tributary of the Irrawaddy River in northern Myanmar. It is distinguished from all other species of the genus Altigena by having a combination of 45–49 lateral-line scales, 12–14 circumpeduncular scales, 17–20 pre-dorsal midline scales, wide head (96.8–138.5% HL), long postorbital length (64.6–81.0 % HL), and short dorsal-fin (length 21.9–26.2% SL).